Bole epiphytic lichens as potential indicators of environmental change in subtropical forest ecosystems in southwest China - Li, S.; Liu, W.; Li, D. (Elsevier BV, 2013)
Lichen epiphytes are applied as excellent environmental indicators worldwide. However, very little is known about epiphytic lichen communities and their response to forest dynamics in subtropical China. This paper proposes the applications of the cover, diversity, and functional traits of epiphytic lichens to assess environmental changes associated with succession in subtropical forests of southwest China. Bole lichens were sampled from 120 plots of eight representative forest types in the Ailao Mountains. Total cover, species richness, diversity and community structure of bole lichens differed significantly among forest types, and the highest cover and diversity occurred in the Populus bonatii secondary forest (PBSF). Sixty-one indicator species were associated with particular forest types and more than 50% occurred in the PBSF. Both cover and diversity of most lichen functional groups varied regularly during forest succession. Lichen pioneer species were not displaced by competitively superior species as succession proceeds and cyanolichens were more prevalent in secondary forests. The results also highlight the importance of habitat variables such as canopy openness, host diversity, forest age, tree size, the size of the largest tree, tree density, and basal area on the lichen community. Consequently, our findings support the notion that epiphytic lichens, in terms of cover, diversity, species composition and functional traits can be used as effective indicators for large-scale and long-term forest monitoring. More importantly, the narrowly lobed foliose group was the best candidate indicator of environmental conditions in this region. The combined application of lichen indicator species and functional groups seemed to be a more reliable and more powerful method for monitoring forest dynamics in subtropical montane ecosystems.